Some methodological aspects of modeling - Kastickaitė, Joana (Lietuvos matematikos rinkinys, 2014)
This article examined the typology of models M. W. Wartofsky, model relationship with modeling. The model uses the idea of realization, and the dynamic aspect of the model as a means to an end.
Keywords: model; analogy; representation; relevant characteristics